1986
DOI: 10.1111/j.1532-5415.1986.tb04223.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Environmental Factors on Glucose Tolerance and Insulin Secretion in a Worker Population

Abstract: The effect of age on glucose tolerance, as differentiated from the effects of obesity, work and leisure physical activity, family history of diabetes, and the use of drugs known to adversely affect glucose tolerance and/or insulin secretion, has been analyzed in 732 factory workers aged 22 to 73 years. Glucose tolerance, as evaluated by the plasma glucose response to 75 g of oral glucose deteriorated with age, associated with an increase in plasma insulin levels. However, the age-related decrease in glucose to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 19 publications
2
43
1
Order By: Relevance
“…The relationship between ageing, body composition, activity and glucose tolerance was also examined in 270 female and 462 male factory workers aged 22-73, none of whom was retired (183). Plasma glucose levels, both fasting and after a glucose load, increased with age, but the correlation between age and total integrated glucose response following a glucose load was weak; in women, only 3% of the variance could be attributed to age.…”
Section: Changes In Glucose Tolerancementioning
confidence: 99%
“…The relationship between ageing, body composition, activity and glucose tolerance was also examined in 270 female and 462 male factory workers aged 22-73, none of whom was retired (183). Plasma glucose levels, both fasting and after a glucose load, increased with age, but the correlation between age and total integrated glucose response following a glucose load was weak; in women, only 3% of the variance could be attributed to age.…”
Section: Changes In Glucose Tolerancementioning
confidence: 99%
“…When adjusted for differences in body weight and physical activity, they found no significant correlation between age and plasma glucose response in men, and differences in age could account for no more than 6% of the variability in glucose response in women. Similarly, when adjusted for differences in weight, physical activity, and use of diabetogenic drugs, age only accounted for 6% of the variance in plasma glucose response to an oral glucose challenge in men and 1% in women in a study of 732 Italian factory workers aged 22-73 years (5). Perhaps the most definitive information in this regard is the results of the Baltimore Longitudinal Study of Aging (6), performed in 743 healthy individuals, comparing glucose tolerance in three age groups: 17-39, 40 -59, and 60 -92 years.…”
mentioning
confidence: 99%
“…The effect of age on insulin secretory function in humans has not been as well defined. On the one hand, the plasma insulin of an oral glucose challenge in older individuals is usually greater than or equal to that in matched younger subjects, and the glucose intolerance reported to occur with aging is not associated with an absolute decrease in plasma insulin concentrations (4,5,8,12). However, it appears that older humans do not have the ability to increase insulin secretion to the degree necessary to prevent some degree of glucose intolerance from developing.…”
mentioning
confidence: 99%
“…The Baltimore Longitudinal Study of Aging also has shown a positive cross-sectional correlation between age and fasting plasma glucose in both men and women (Muller et al, 1996;Shimokata et al, 1991). Zavaroni et al (1986) demonstrated an age-related increase in fasting glucose levels in Italian factory workers; this was signi®cantly reduced in women after adjustments were made for the presence of other agerelated variables. Small increases in fasting glucose levels with age were noted in 4170 men and women living in suburban California (0.7 mgadladecade in men; 2.0 mgadladecade in women) (Barrett-Connor, 1980).…”
Section: Fasting Glucosementioning
confidence: 97%
“…However, the decline from mid-life to old age (60 ± 92 y) was still in¯uenced by chronological age. In a population of Italian factory workers (Zavaroni et al, 1986) age-related environmental factors (obesity, physical activity, diabetogenic drug use) accounted for a large portion of the decline in glucose tolerance in women, but not in men. Maneatis et al (1982) found that after adjustment for obesity and activity there was an independent effect of age on the decline in glucose tolerance in women.…”
Section: Confounding Effects On the Relationship Of Age And Glucose Tmentioning
confidence: 98%